Novice Teachers: The Process of "Anchoring" in the Teaching Profession - Hanna Kędzierska (University of Lower Silesia, 2015)
The process of novice teacher's transition/integration is rarely the subject of consideration and research in the education field in general and teacher training in particular. The dominant, functionalist manner of thinking about the professional role focuses mainly on problems associated with the teacher's adaptation to the workplace and is usually limited to a statistical diagnosis (more or less successful) of how the "newcomer" conformed to existing, externally adopted standards. Such analyses, however, ignore various contexts that are extremely important from the point of view of becoming a teacher, i.e., contexts formed at the intersections of interactions between individual and individual, individual and professional group, and individual and institutional culture. This paper will present preliminary results of research devoted to the process of becoming a teacher in the period of transition/integration of teachers (novices) into their professional group, based on concepts that are "alien" to traditional research in teacher training: symbolic interactionism and migration theories.